THE INFLUENCE OF SERVICE QUALITY AND CUSTOMER VALUE ON PURCHASE DECISIONS IN GRATING SALES AT CV. CAHAYA TERANG - Arifin, Muchammad Bustanil; Herdinata, Christian (International Journal of Review Management Business and Entrepreneurship (RMBE), 2025)
This research seeks to investigate the effect of Service Quality and Customer Value on Purchase Decisions, specifically in the context of grating product sales at CV Cahaya Terang. The variables studied include Service Quality (SQ), Customer Value (CV), and Purchase Decision (PD). Service Quality has six indicators, namely responsiveness, reliability, assurance, empathy, tangibility, and physical evidence. Customer Value has four indicators, namely product quality, functional benefits, emotional benefits, and price. Purchase Decision has three indicators, namely stability in the product, buying habits, and recommendations to others. The analysis tool used is Partial Least Square (PLS). The population in this study is 80 customers of CV Cahaya Terang grating companies, with a saturated sampling technique. The results show that Service Quality has a significant effect on Purchase Decisions, with the biggest determining indicator being responsiveness. Customer Value also has a significant influence on Purchase Decisions, with the biggest determining indicator being product quality. In addition, Customer Value has been proven to mediate the influence of Service Quality on Purchase Decisions.